Linear Copolymers Based on Choline Ionic Liquid Carrying Anti-Tuberculosis Drugs: Influence of Anion Type on Physicochemical Properties and Drug Release - Niesyto, Katarzyna (Int J Mol Sci, 2020)
In this study, drug nanocarriers were designed using linear copolymers with different contents of cholinium-based ionic liquid units, i.e., [2-(methacryloyloxy)ethyl]trimethylammonium chloride (TMAMA/Cl: 25, 50, and 75 mol%). The amphiphilicity of the copolymers was evaluated on the basis of their critical micelle concentration (CMC = 0.055–0.079 mg/mL), and their hydrophilicities were determined by water contact angles (WCA = 17°–46°). The chloride anions in the polymer chain were involved in ionic exchange reactions to introduce pharmaceutical anions, i.e., p-aminosalicylate (PAS(−)), clavulanate (CLV(−)), piperacillin (PIP(−)), and fusidate (FUS(−)), which are established antibacterial agents for treating lung and respiratory diseases. The exchange reaction efficiency decreased in the following order: CLV(−) > PAS(−) > PIP(−) >> FUS(−). The hydrophilicity of the ionic drug conjugates was slightly reduced, as indicated by the increased WCA values. The major fraction of particles with sizes ~20 nm was detected in systems with at least 50% TMAMA carrying PAS or PIP. The influence of the drug character and carrier structure was also observed in the kinetic profiles of the release processes driven by the exchange with phosphate anions (0.5–6.4 μg/mL). The obtained polymer-drug ionic conjugates (especially that with PAS) are promising carriers with potential medical applications.